Conceptual Analogies Between Multi-Scale Feeding and Feedback Cycles in Supermassive Black Hole and Cancer Environments - Santoni, Matteo; Tombesi, Francesco; Cimadamore, Alessia; Montironi, Rodolfo; Piva, Francesco (Frontiers in Oncology, 2021)
Adopting three physically-motivated scales ("micro" – "meso” – “macro”, which refer to mpc – kpc – Mpc, respectively) is paramount for achieving a unified theory of multiphase active galactic nuclei feeding and feedback, and it represents a keystone for astrophysical simulations and observations in the upcoming years. In order to promote this multi-scale idea, we have decided to adopt an interdisciplinary approach, exploring the possible conceptual similarities between supermassive black hole feeding and feedback cycles and the dynamics occurring in human cancer microenvironment.